Extrafollicular CD4+ T-B interactions are sufficient for inducing autoimmune-like chronic graft-versus-host disease. Issue 1 (December 2017) - Deng, Ruishu; Hurtz, Christian; Song, Qingxiao; Yue, Chanyu; Xiao, Gang; Yu, Hua; Wu, Xiwei; Muschen, Markus; Forman, Stephen; Martin, Paul; Zeng, Defu
Abstract Chronic graft-versus-host disease (cGVHD) is an autoimmune-like syndrome mediated by pathogenic CD4+ T and B cells, but the function of extrafollicular and germinal center CD4+ T and B interactions in cGVHD pathogenesis remains largely unknown. Here we show that extrafollicular CD4+ T and B interactions are sufficient for inducing cGVHD, while germinal center formation is dispensable. The pathogenesis of cGVHD is associated with the expansion of extrafollicular CD44hi CD62lo PSGL-1lo CD4+ (PSGL-1lo CD4+ ) T cells. These cells express high levels of ICOS, and the blockade of ICOS/ICOSL interaction prevents their expansion and ameliorates cGVHD. Expansion of PSGL-1lo CD4+ T cells is also prevented by BCL6 or Stat3 deficiency in donor CD4+ T cells, with the induction of cGVHD ameliorated by BCL6 deficiency and completely suppressed by Stat3 deficiency in donor CD4+ T cells. These results support that Stat3- and BCL6-dependent extrafollicular CD4+ T and B interactions play critical functions in the pathogenesis of cGVHD. Chronic graft-versus-host disease (cGVHD) is mediated by specific CD4 and B cells, but the relative contribution of extrafollicular and germinal centre (GC) T-B interaction is unclear. Here the authors show that the extrafollicular expansion of a specific CD4 T subset is sufficient for inducing cGVHD while GC is dispensable.